Mechanism of Paeoniflorin on ANIT-Induced Cholestatic Liver Injury Using Integrated Metabolomics and Network Pharmacology - Chen, Lisheng; Zhao, Xu; Wei, Shizhang; Ma, Xiao; Liu, Honghong; Li, Jianyu; Jing, Manyi; Wang, Min; Zhao, Yanling (Frontiers in Pharmacology, 2021)
Background: Paeoniflorin (PF), the major active compound isolated from the roots of Paeonia lactiflora Pall., has been used in the treatment of severe hepatic diseases for several decades and displays bright prospects in liver protective effect. However, its biological mechanism that regulates bile acid metabolism and cholestatic liver injury has not been fully elucidated. Our study aims to investigate the mechanism by which PF in the treatment of cholestatic liver injury using a comprehensive approach combining metabonomics and network pharmacological analysis. Methods: The hepatoprotective effect of PF against cholestasis liver injury, induced by α-naphthylisothiocyanate (ANIT), was evaluated in rats. The serum biochemical indices including ALT, AST, TBA, TBIL, ALP, ALB and the pathological characteristics of the liver were analyzed. Moreover, UHPLC-Q-TOF was performed to explore the feces of rats with ANIT-induced cholestatic liver injury treated with PF and the potential biomarkers were screened by metabonomics. The targets for the regulation of potential biomarkers by PF were screened by network pharmacology, and then the relevant key targets were verified by immunohistochemical approach. Results: PF significantly improved serum indexes and alleviated liver histological damage. Metabolomics analyses showed that the therapeutic effect of PF is mainly associated with the regulation of 13 metabolites involved in 16 metabolic pathways. The “PF-targets-metabolites” interaction network was constructed, and then 5 key targets including CDC25B, CYP2C9, MAOB, mTOR and ABCB1 that regulated the potential biomarkers were obtained. The above five targets were further verified by immunohistochemistry, and the results showed that PF significantly improved the expression of key proteins regulating these biomarkers. Conclusion: Our study provides direct evidence for the modulatory properties of PF treatment on ANIT-induced cholestatic liver injury using metabolomics and network pharmacology analyses. PF exhibits favorable pharmacological effect by regulating related signal pathways and key targets for biomarkers. Therefore, these findings may help better understand the complex mechanisms and provide a new and effective approach to the treatment of cholestatic liver injury.